Choosing Wisely in oncology in Latin America: what SLACOM does not recommend in the care of cancer patients in Latin America - Ismael, J (2024)
Choosing Wisely is an initiative by the American Board of Internal Medicine (ABIM) and ABIM Foundation to deter unnecessary medical treatments and procedures. Faced with the burden of modern technologies and treatments, it is crucial to identify practices lacking value in daily care. The Latin American and Caribbean Society (SLACOM), comprising cancer control experts, deems it vital to tailor this initiative for enhancing cancer care in the region. Through a modified DELPHI methodology involving two rounds of electronic questionnaires and a hybrid meeting to discuss key points of contention, ten essential recommendations were identified and prioritised to avoid harmful oncology procedures in our region. These consensus-based recommendations, contextualised for Latin America, have been compiled and shared to benefit patients. The Scientific Committee, consisting of prominent oncologists and health experts, collaborates remotely to drive this project forward.